Analisis Penerapan Perencanaan Pajak Penghasilan Pasal 21 Sebagai Strategi Penghematan Pembayaran Pajak Perusahaan Pada PDAM Tirta Mangutama Kabupaten Badung - Sintya Wiranti Cahyono; Luh Kade Datrini; I Gusti Ayu Intan Saputra Rini (Jurnal Riset Akuntansi Warmadewa, 2022)
PDAM Tirta Mangutama Badung Regency is a BUMD company oriented towards the distribution of clean water to the people of Badung Regency. Besides being a regional owned business but also PDAM is a profit business that generates profits. Businesses that can optimize profits are by efficiently adjusting income tax article 21. This is based on PDAM has 322 permanent employees, so with many workers, PDAM has a high cost to pay workers' rights. The purpose of this study is to find out the application of the PPh method article 21 employees in PDAM Tirta Mangutama Badung and match the amount of PDAM tax between the methods applied, compared to other cutting methods. The result of the study is the method of cutting PPh Article 21 using the gross up method. If using the gross up method PDAM Tirta Mangutama Badung deposited taxes worth Rp.271,382,152. while when using the gross method or the net method the value of taxes owed for PPh Article 21 worth Rp.271,248,547.